Experience of Menstrual Pain in Late Adolescence: Scale and Implementation at Home (JURNAL KEPERAWATAN, 2022)
Pain is a perception of discomfort that causes barriers to physical activity. Pain can occur physiologically in women who will experience menstruation or during menstruation. Menstrual pain is felt as a lower abdominal cramping sensation that has different characteristics for each individual. The purpose of this study was to describe the experience of menstrual pain in late adolescents (aged 17-20 years). This study is an online survey of 70 nursing students who experienced dysmenorrhea through accidental sampling. This experience survey contains the incidence of dysmenorrhea, pain scale, and pain management. The results showed that the pain category based on the scale was mild pain (32.3%), moderate pain (44.3%), and severe pain (21.4%). Implementation of pain includes rest-sleep (35.7%), warm compresses (27.1%), massage and pressure (18.6%), drinking water (18.6%), positioning (12.9%), holding pain without any action (7.1%), taking analgesic drugs (0.1%), and increasing physical activity (0.04%). There are 68.6% of respondents succeeded in reducing pain through their implementation. Conclusion: the experience of dysmenorrhea in late adolescence is in the moderate pain category. The most widely used implementations is overcoming pain are rest-sleep and warm compresses.